Kallistatin inhibits tumour progression and platinum resistance in high-grade serous ovarian cancer - Huan Wu; Rongrong Li; Zhiwei Zhang; Huiyang Jiang; Hanlin Ma; Cunzhong Yuan; Chenggong Sun; Yingwei Li; Beihua Kong (BMC, 2019)
Abstract Ovarian cancer is the most lethal gynaecologic malignancy. Although there are various subtypes of ovarian cancer, high-grade serous ovarian cancer (HGSOC) accounts for 70% of ovarian cancer deaths. Chemoresistance is the primary reason for the unfavourable prognosis of HGSOC. Kallistatin (KAL), also known as SERPINA4, is part of the serpin family. Kallistatin has been discovered to exert multiple effects on angiogenesis, inflammation and tumour progression. However, the roles and clinical significance of kallistatin in HGSOC remain unclear. Here, we showed that kallistatin was significantly downregulated in HGSOC compared to normal fallopian tube (FT) tissues. Low expression of kallistatin was associated with unfavourable prognosis and platinum resistance in HGSOC. Overexpression of kallistatin significantly inhibited proliferation and metastasis, and enhanced platinum sensitivity and apoptosis in ovarian cancer cells. Collectively, these findings demonstrate that kallistatin serves as a prognostic predictor and provide a potential therapeutic target for HGSOC.